Changes in soil and vegetation properties under different land uses in Northern Scandinavia - Bolter,Manfred; Moller,Rolf; Peth,Stephan (2006)
P(論文) We studied changes in vegetation, soil microbiology and soil properties during a 3 years study in a Fennoscandia tundra. The test sites were located at the border between Norway and Finland, a region which is divided by a fence to different areas of land use by reindeer herding. The Norwegian site acts as winter pasture only, the Finnish site is under use all the year. Due to shifts of the fence some years ago, an area of recover was found. Reindeer grazing and trampling changed not only vegetation cover, mainly from lichen heaths in Norway to grass and shrub land at the Finnish side. This had also consequences on soil properties, the microbial community and soil respiration. Differences in these items, however, are not directly to changes in vegetation cover; more dangerous are trampled and probably highly grazed spots which show barren soils. Main effect to soil respiration is temperature, which shows significant higher levels at the Finnish side, which leads to higher evaporation, thus lower moisture and thereof reduced microbial activity. departmental bulletin paper